Pemberdayaan Remaja Desa Gumantar Melalui Program Kajian Keagamaan untuk Meningkatkan Aspek Spiritualitas - Muammar Qadafi; Neneng Agustiningsih (Participative Journal: Jurnal Pengabdian Pada Masyarakat, 2023)
This service activity is motivated by changes in the behavior of adolescents in Gumantar Village who are starting to show negative things, such as brawls or fights and speaking impolitely to older people. This behavior of course undermines the spiritual values ​​that exist in the teenager's personality. The method used in this service is Participatory Action Research which involves students who are carrying out participatory work lectures as the subject of the activity. The results show that the youth forum is a forum or space for youth to receive religious guidance and training that can improve their skills so that the deviant behavior that has appeared so far can be minimized.